Analysis of Relocation, Infrastructure and Islamic Business Ethics on Consumer Decisions through Consumer Behavior at Pasar Baru Mandailing Natal - Nasution, Rizka; Batubara, Maryam; Bi Rahmani, Nur Ahmadi (Journal La Sociale, 2024)
This research aims to analyze the influence of trader relocation, market infrastructure, and Islamic business ethics on consumer decisions and satisfaction at Pasar Baru Mandailing Natal. The research methods used involved surveys, interviews, and path analysis. Research findings show that trader relocation, supported by adequate infrastructure and the application of Islamic business ethics, together create a better trading environment and positively influence consumer decisions and satisfaction. The results of path analysis show that these three factors interact with each other and contribute to shaping consumer perceptions and behavior. The practical implications of this research include the importance of effective communication during the relocation process, sustainable investment in market infrastructure, the implementation of Islamic business ethics as a standard, and a holistic approach to market management.